PENERAPAN MODEL TATA KELOLA LKMS BERBASIS MAQOSHID SYARIAH DALAM MENSEJAHTERAKAN ANGGOTA DI KSPPS MAWAR SIMO SUNGELEBAK LAMONGAN - Thoifatul Munawaroh; Syuhada Syuhada; Intan Ayu (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study was motivated by the importance of implementing governance in Islamic Microfinance Institutions (IMFIs) that is oriented not only toward financial performance but also toward achieving the objectives of maqashid sharia, particularly hifdzul mal (the protection of wealth), in improving members' welfare. KSPPS Mawar Simo Sungelebak Lamongan, as one of the Islamic Microfinance Institutions, plays a strategic role in providing Sharia-compliant financial services based on the principles of transparency, accountability, responsibility, fairness, and Sharia compliance. This study aims to analyze the implementation of a maqashid sharia-based governance model in improving the welfare of members at KSPPS Mawar Simo Sungelebak Lamongan. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing techniques, while data validity was ensured through source triangulation and technique triangulation. The results indicate that KSPPS Mawar Simo Sungelebak Lamongan has implemented maqashid sharia-based governance through the principles of transparency, accountability, responsibility, fairness, and Sharia compliance in its operational activities. The implementation of hifdzul mal is reflected in the trustworthy management of funds, appropriate financing distribution, supervision of fund utilization, and efforts to maintain the sustainability of members' businesses. The implementation of this governance model has positively contributed to members' welfare, as indicated by improved access to Sharia financing, business development, increased income, and stronger members' trust in the institution.